CPR-Induced Consciousness during Ventricular Fibrillation: Case Report and Literature Review - Xiaoqing Zhou; Boru Sun (Emergency Medicine International)
Introduction. Over the years, numerous studies have suggested the occurrence of a peculiar phenomenon known as “CPRIC” during the revival process. The revelation of this phenomenon has ignited widespread discussion and investigation, yet many enigmas remain unsolved. This study describes the case of a 52-year-old man diagnosed with acute anterior myocardial infarction, who experienced ventricular fibrillation while awaiting further treatment. Despite ultimately not regaining spontaneous circulation, he remained conscious for a period during chest compressions and showed signs of resistance. Methods. PubMed and Web of Science were searched until July 11, 2024. We included original studies and case reports relevant to CPRIC. For case reports, we extracted information on the author (year), country, patients, location, compression, signs of CPRIC, treatment of CPRIC, and patient outcomes. For other studies, we included the author (year), country, participants, and results. The extracted data were synthesized using a narrative approach. Results. Of 3038 articles, 32 were included, i.e., 18 case reports (24 cases), 9 cross-sectional surveys, and 5 cohort studies. In CPRIC cases, patients exhibited various manifestations including opening their eyes, speaking, and moving. Other included studies explored healthcare workers’ awareness and experiences of CPRIC, the incidence and manifestations of CPRIC, the impact of CPRIC on patient outcomes, memories and perceptions of cardiac arrest indicating consciousness, the effects of CPRIC on rescuers, and the management of CPRIC. Conclusions. There is an urgent need to establish a globally recognized definition of CPRIC. It is crucial to develop clear algorithms that focus not only on identifying this phenomenon but also on determining the best approaches to manage it. Furthermore, CPRIC can cause multiple interruptions during CPR, making it essential to differentiate whether these interruptions are due to CPRIC or indicative of a return of spontaneous circulation.